Explaining the Basics and Principles of maintenance and upgrading urban streets with the approach of Islamic teachings and Iranian culture (Imam Reza Zaman Street of Mashhad) - mahdi moharreri; mohammad naghizade; fereshte ahmadi; shirin toghyani (تحقیقات کاربردی علوم جغرافیایی)
One of the issues facing today's cities in Iran is the issue of maintaining and upgrading existing streets. The way of managing theses streets and dealing with them has caused various problems in different aspects of cities. The purpose of this research is investigating the principles of maintenance and promotion of urban streets with a focus on Islamic teachings and Iranian culture. This research also explains some ways to improve the quality of urban streets using Islamic teachings and Iranian culture. Gathering information was done through observation, field study and documentary studies. Using content analysis methods, documenting and graphical analysis, information and data were analyzed. The quality of the cities depends on the quality of the streets and the quality of the streets is also based on the details of the streets. After designing and constructing urban streets, they need attention, maintenance and promotion in order to be always attractive and desirable for citizens. The results of this study indicate neglecting the indigenous material, art, culture, religion, needs and interests of citizens which has led to the construction of unqualified urban spaces in the metropolitan areas of today's Iranian cities. This research did not seek to provide a template for urban streets designing, but it is in direction of developing principles of planning and designing urban streets based on Islamic teachings and Iranian culture. In addition to having appearances according to Islamic teachings and Iranian culture, desirable street for Iranian citizens should also be Islamic and Iranian internally. With Just the correctness of appearances it can be said that only hypocrisy is obtained, but with internal reforming, honesty can be created in urban spaces.